Pengembangan Media Pembelajaran Pengembangan Media Pembelajaran Flippbook Model Hybrid pada Pembelajaran Praktikum Kimia Dasar dalam Meningkatkan Keterampilan Proses Sains Mahasiswa: Pengembangan Media Pembelajaran Flippbook Model Hybrid pada Pembelajaran Praktikum Kimia Dasar dalam Meningkatkan Keterampilan Proses Sains Mahasiswa - Eva Pratiwi Pane; Anita Debora Br Simangunsong; Christa Voni Roulina Sinaga (UNIB Press, 2023)
Educators need to innovate in learning by utilizing one of the technology-based learning media using the right learning model so that the learning process becomes effective and meaningful. The purpose of this research was to develop a flipbook learning media hybrid model in basic chemistry practicum learning in improving students' science process skills. This type of research was research and development with the model proposed by Borg & Gall using the 4D model. Material and media expert validation was used to assess the feasibility of the media. The practicality and effectiveness of the media were tested in small groups. The research instrument consisted of observation sheets, practicum reports and questionnaires. The data consists of qualitative and quantitative where collected using a concurrent or concurrent model. Quantitative data was processed into percentages and interpreted to be the level of feasibility and the level of practicality of the media. Effectiveness is a media capability that is developed to support the improvement of students' science process skills. Qualitative data describes students' science process skills that were observed while students are participating in media trials. Based on the research results obtained, it can be concluded that flipbook learning media with a hybrid model in basic chemistry practicum learning that has been developed is very feasible and practical to use in basic chemistry practicum learning and can be used to train students' science process skills independently or in a supervised manner.